1991
DOI: 10.1177/002221949102400208
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Diagnostic Category of Attention Deficit Disorder Without Hyperactivity

Abstract: The validity of the diagnostic category of Attention Deficit Disorder Without Hyperactivity (ADD/WO) has been the subject of debate since it was first introduced in DSM-III. The differentiation of two syndromes of ADD is supported by factor analytic studies that indicate two dimensions of maladjustment: (1) inattention and disorganization, and (2) motor hyperactivity and impulsive responding. Cluster analyses of these two dimensions have yielded two profiles of deviance that correspond to the DSM-III subtypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 23 publications
6
94
1
4
Order By: Relevance
“…Although the reduction of false-positive diagnoses is a laudable goal, it is not clear why help would not be provided to a child who meets all other criteria for ADHD but has serious impairment in only 1 setting. In combination with the previous literature [5], the current results suggest that the validity of the cross-setting impairment criterion should be systematically evaluated in future studies to clarify the costs and benefits of its inclusion as a diagnostic criterion in the DSM-5 or other future diagnostic systems.…”
Section: Significant Impairment Across Multiple Settingsmentioning
confidence: 52%
See 2 more Smart Citations
“…Although the reduction of false-positive diagnoses is a laudable goal, it is not clear why help would not be provided to a child who meets all other criteria for ADHD but has serious impairment in only 1 setting. In combination with the previous literature [5], the current results suggest that the validity of the cross-setting impairment criterion should be systematically evaluated in future studies to clarify the costs and benefits of its inclusion as a diagnostic criterion in the DSM-5 or other future diagnostic systems.…”
Section: Significant Impairment Across Multiple Settingsmentioning
confidence: 52%
“…This criterion was included to ensure that individuals who received a diagnosis of ADHD were experiencing pervasive difficulties, and to minimize the chance that ADHD would be overdiagnosed due to inflated ratings by a single distressed rater. However, ADHD is the only DSM-IV disorder that requires impairment to be documented in multiple settings, and only a handful of studies have tested the validity of this criterion [5]. Table 2 summarizes the results of analyses that were conducted in our community sample to test the specific impact of the cross-setting impairment criterion on the prevalence of ADHD.…”
Section: Significant Impairment Across Multiple Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the shyness literature, it is common to find relationships between shyness and anxiety, specifically social anxiety (Eisenberg et al, 1995; LONELINESS, SHYNESS, AND DEPRESSION Lahey & Carlson, 1991;Lawton, Powell, Kleban, & Dean, 1993;Neto, 1992). Indeed, Anderson and Harvey (1988) showed that the most popular self-report measures of shyness and social anxiety are indistinguishable.…”
Section: Antecedents Of Shynessmentioning
confidence: 99%
“…Furthermore, the inattentive subtype of ADHD is more strongly associated with internalizing problems like depression and anxiety than the hyperactive/impulsive subtype of ADHD (Hinshaw, 1994;Lahey & Carlson, 1992;Lahey et al, 1988;Lahey, Schaughency, Hynd, Carlson, & Nieves, 1987). In sum, it may be possible that in some cases co-occurring ADHD-MDD represents a third disorder characterized by SCT.…”
Section: Explanations Concerning Inaccurate Diagnosticmentioning
confidence: 99%